CHELOSCOPY-A UNIQUE FORENSIC TOOL - M., Sharma S.; Shalini, Krishnan; Akshari, Anchan (Journal of Health and Allied Sciences NU, 2013)
Identity is a characteristic that is unique to every individual. It is an important factor in cases of theft, criminal investigations of the dead or missing, mass disasters both by natural causes and by criminal intent – with this as our day to day reality, the establishment and verification of human identity has become extremely important. DNA and fingerprints are clearly the favored methods of identification, but, they require a prior record and verifiable baseline for comparison. When these tools cannot be used it is necessary to employ those biological factors with higher variation and lower diagnostic probability. Chelioscopy is one among them.
Keywords: Cheilioscopy; forensic odontology; lip prints